ANALISIS KETERKAITAN NETWORK PHAMACOLOGY SENYAWA METABOLIT SEKUNDER Abrus precatorius L. SECARA IN SILICO - Khoirunnisa, Azka; Jamil, Ahmad Shobrun; Muchlisin, M. Artabah (Jurnal Penelitian Farmasi Dan Herbal, 2024)
Cancer remains a global health challenge, prompting extensive research efforts worldwide. Lung cancer, the second most diagnosed cancer, presents a particularly grim survival rate. In Indonesia, cancer incidence ranks significantly, with millions affected and hundreds of thousands succumbing to the disease annually. Traditional medicine persists as a preferred option among many, perceived as safer and more affordable. Abrus precatorius L., an ancient medicinal plant, holds promise in this regard, with a rich history of use and a diverse range of pharmacological activities, including anti-cancer properties. Employing in silico modeling and network pharmacology, this study explores the interaction between Abrus precatorius L. compounds and various proteins associated with cancer. Through bioinformatics tools and databases, 27 bioactive compounds are identified and their physicochemical properties assessed, ensuring adherence to pharmacological guidelines. The study predicts potential protein targets for Abrus precatorius L. compounds, revealing interactions with 453 proteins, including those implicated in cancer pathways. Further analysis using StringDB and DISEASES database establishes protein-protein interaction networks, highlighting key proteins like EGFR and TERT, pivotal in multiple cancer types. The study validates the compounds' adherence to Lipinski's Rule of Five, indicating their potential for pharmacological activity and oral absorption. False Discovery Rate (FDR) analysis confirms significant associations between Abrus precatorius L. compounds and various cancers, further underscoring their therapeutic potential. In conclusion, Abrus precatorius L. compounds, particularly targeting EGFR and TERT proteins, emerge as promising candidates for cancer treatment. Their diverse pharmacological activities and interactions with key cancer-related proteins pave the way for further exploration and development of these compounds as alternative medicinal agents. In vitro and in vivo studies are warranted to validate their efficacy, particularly in addressing the complexities of different cancer types. Ultimately, this research offers valuable insights into leveraging natural compounds for combating cancer, addressing a critical need in global healthcare.